2023
DOI: 10.1021/jacs.2c11757
|View full text |Cite
|
Sign up to set email alerts
|

Oxygen-Enhanced Atom Transfer Radical Polymerization through the Formation of a Copper Superoxido Complex

Abstract: In controlled radical polymerization, oxygen is typically regarded as an undesirable component resulting in terminated polymer chains, deactivated catalysts, and subsequent cessation of the polymerization. Here, we report an unusual atom transfer radical polymerization whereby oxygen favors the polymerization by triggering the in situ transformation of CuBr/ L to reactive superoxido species at room temperature. Through a superoxido ARGET-ATRP mechanism, an order of magnitude faster polymerization rate and a ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
38
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(41 citation statements)
references
References 73 publications
2
38
0
1
Order By: Relevance
“…[46][47][48] Furthermore, it has been reported that both oxygen and water might be beneficial to ATRP. 32,45,49 For context, despite oxygen and water traces, ARGET ATRP of styrene with H 2 AA/Na 2 CO 3 , gave fairly good results in terms of Đ and ΔM n (the latter being an index of deviation from the theoretical value of M n ). 17,49 By swapping H 2 AA for its acetonide counterpart, conversion increased at the cost of a slight loss of control (both ΔM n and Đ were higher, compare entries 1 and 2 in Table 1).…”
Section: Polymer Chemistry Papermentioning
confidence: 98%
See 1 more Smart Citation
“…[46][47][48] Furthermore, it has been reported that both oxygen and water might be beneficial to ATRP. 32,45,49 For context, despite oxygen and water traces, ARGET ATRP of styrene with H 2 AA/Na 2 CO 3 , gave fairly good results in terms of Đ and ΔM n (the latter being an index of deviation from the theoretical value of M n ). 17,49 By swapping H 2 AA for its acetonide counterpart, conversion increased at the cost of a slight loss of control (both ΔM n and Đ were higher, compare entries 1 and 2 in Table 1).…”
Section: Polymer Chemistry Papermentioning
confidence: 98%
“…The cuvette contains [base] : [H 2 AAIPI] : [TPMA] : [CuCl 2 ] = 100 : either 16.7 (green) or 0 (red and blue curves) : 2.51 : 1.67 mol% with respect to the base (2.12 mmol L −1 ). Interestingly, a transient peak appears at 450 nm that can be explained by the formation of oxygen-copper-TPMA complexes 39,45. (E) Absorbance at 800 nm vs. time, one acquisition every two minutes.…”
mentioning
confidence: 99%
“…17 However, a very recent work demonstrated the positive role of oxygen as it can promote an unusual atomtransfer radical polymerization. 29 To our surprise, oxygen was also found to play a positive role in promoting the luminescence in our work. To the best of our knowledge, this is the first report utilizing oxygen as a radical relayer for visualizing mechanoradical damages in polymeric materials.…”
Section: Introductionmentioning
confidence: 99%
“…It has to be noted that, generally, oxygen is considered to have a negative effect as it could terminate radical reactions. It therefore greatly restricts the usage of mechanoradicals . However, a very recent work demonstrated the positive role of oxygen as it can promote an unusual atom-transfer radical polymerization . To our surprise, oxygen was also found to play a positive role in promoting the luminescence in our work.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, high amounts of catalyst are typically needed for a successful polymerization. To overcome both barriers, a number of alternative ATRP approaches have recently been developed, including eATRP, 11,12 photoATRP, [13][14][15][16] ARGET-ATRP, 17,18 and, (P)ICAR-ATRP. 19,20 A common feature of these methodologies is that they require a stimulus or an additive to in situ re-generate the active catalyst and as a result they can operate at significantly lower catalyst concentrations.…”
Section: Introductionmentioning
confidence: 99%